Optimisation of dry bean (Phaseolus vulgaris L.) seed production under greenhouse conditions - Hammes, Pieter Snyman, 1941- (University of Pretoria, 2013)
Dissertation (MSc Agric (Agronomy))--University of Pretoria, 2005.